2017
DOI: 10.1289/ehp293
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Use of Walking Loops in Neighborhood Parks: A National Study

Abstract: Background:Previous studies indicate that the design of streets and sidewalks can influence physical activity among residents. Park features also influence park use and park-based physical activity. Although individuals can walk on streets and sidewalks, walking loops in parks offer a setting to walk in nature and to avoid interruptions from traffic.Objectives:Here we describe the use of walking loops in parks and compare the number of park users and their physical activity in urban neighborhood parks with and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
2
17
0
Order By: Relevance
“…It may be because the combined looped walkway with a systematic structure promoted walk activity. This finding was supported by previous studies showing walking loops can increase users' walk activity [61,62].…”
Section: Setting Types and Physical Activity Levelsupporting
confidence: 86%
“…It may be because the combined looped walkway with a systematic structure promoted walk activity. This finding was supported by previous studies showing walking loops can increase users' walk activity [61,62].…”
Section: Setting Types and Physical Activity Levelsupporting
confidence: 86%
“…The national study found that the facility generating the most MVPA time for adults and seniors was the walking loop, which is designed to facilitate continuous movement along a pathway (as opposed to sidewalks, which are typically shorter and designed to connect different sections of a park) (Cohen, Han, Nagel, et , 2016). Researchers found that parks with walking loops had 80 percent more users than parks without, and levels of physical activity were 90 percent higher (Cohen, Han, Evenson, et al, 2017). There was also a "spillover" effect in that parks without walking loops had higher rates of overall use throughout the park than other loops did.…”
Section: Numbers and Types Of Facilitiesmentioning
confidence: 99%
“…After analyzing data for more than 170 parks, Cohen and colleagues found that those with walking loops had more users, more of whom engaged in moderate to vigorous physical activity, than those without these amenities. 1 …”
mentioning
confidence: 99%
“…The authors conclude that walking loops may be an affordable way to increase a park’s appeal and health benefits. 1 …”
mentioning
confidence: 99%